2003
DOI: 10.21099/tkbjm/1496164559
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Representation of Generalized Tempered Distributions of Exponential Growth by Wavelets

Abstract: Abstract. The analytic representation of the generalized tempered distributions of e MðkxÞ -growth with restricted order, K r0 M ðRÞ, is given in terms of series of analytic wavelets. These series converge uniformly on compact subsets of the upper and lower half planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the meantime, the tempered distributions of polynomial growth were extended to tempered distributions of | | -growth, K 1 (R), in [5,6] and | | -growth, K (R), in [7,8] or -growth, K (R), in [9,10], where the function ( ) grows faster than any linear functions as | | . We have considered the analytic representation of tempered distributions of -growth with restricted order, K (R), by wavelets [11]. Also, we have shown that the multiresolution expansions of K (R) converges pointwise to the value of the distribution where it exists [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the tempered distributions of polynomial growth were extended to tempered distributions of | | -growth, K 1 (R), in [5,6] and | | -growth, K (R), in [7,8] or -growth, K (R), in [9,10], where the function ( ) grows faster than any linear functions as | | . We have considered the analytic representation of tempered distributions of -growth with restricted order, K (R), by wavelets [11]. Also, we have shown that the multiresolution expansions of K (R) converges pointwise to the value of the distribution where it exists [12].…”
Section: Introductionmentioning
confidence: 99%